Research on evaluation of enterprise project culture based on Denison model - Yucheng Zeng; Maozhu Jin; Can Guo; Zhiwei Zhang (Journal of Industrial Engineering and Management (JIEM), 2015)
Purpose: The purpose of this paper is to build enterprise project culture evaluation model and search for the best evaluation method for Chinese enterprise project culture on the basis of studying and drawing lessons from enterprise culture evaluation theory and method at home and abroad. Design/methodology/approach: Referring to the Denison enterprise culture evaluation model, this paper optimizes it according to the difference of enterprise project culture, designs the enterprise project culture evaluation model and proves the practicability of the model through empirical. Finding: This paper finds that its more applicable to use the Denison model for enterprise project culture evaluation through the comparative analysis of domestic and foreign enterprise culture evaluation theory and method, the systematic project culture management framework of Chinese enterprises has not yet formed through empirical research, and four factors in enterprise project culture have important influence on project operation performance improvement. Research limitations/implications: The research on evaluation of enterprise project culture based on Denison model is a preliminary attempt, the design of evaluation index system, evaluation model and scale structure also need to be improved, but the thinking of this paper in this field provides a valuable reference for future research. Practical Implications: This paper provides the support of theory and practice for evaluating the present situation of enterprise project culture construction and analyzing the advantages and disadvantages of project culture, which contributes to the "dialectical therapy" of enterprise project management, enterprise management and enterprise project culture construction. Originality/value: The main contribution of this paper is the introduction of Denison enterprise culture model. Combining with the actual situation of enterprises, this paper also builds the evaluation model for enterprise project culture, which is helpful to promote the construction and development of Chinese enterprise project culture.
Keywords: 650; enterprise culture; project culture; evaluation model